(untitled) (Bangladesh Journal of Medical Science, 2024)
Background: Recently, there has been a tendency to decrease the results of domestic skiers, in order to solve this problem, it is necessary to change the training approach in the preparatory period before the competition. The purpose of the study: Improving the physical fitness of skiers using special training tools. Materials and methods: In the Russian Federation, a pedagogical experiment was conducted in the village of Korshik. It was attended by teenagers aged 13-14 who were engaged in cross-country skiing. A total of 40 children participated (20-control and 20-experimental groups). The difference between the experimental group was the use of special exercises at the preparatory stage of training. The study used control standards that show the level of physical qualities, such as pull-ups, squats, long jumps, simulated 100m lifting and 500m running. Results: The children from the experimental group significantly improved their performance in the pull-up test (22.2%; p<0.05), squats (5.9%; p<0.05), long jumps on two legs (6.8%; p<0.05), 100-simulated lifting per meter (7.8%; p<0.05) and running at 500 meters (4.2 %, p<0.05). At the same time, children from the control group were unable to show significant improvements in physical fitness (p>0.05). Conclusión: During the preparatory period of ski racers, it is recommended to include special exercises that will significantly increase the level of physical qualities. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 818-825